"El uso del software en el proceso enseñanza aprendizaje de lenguaje en época de pandemia en los niños de educación inicial II, en la escuela de educación básica Benjamín Franklin, de la ciudad de Riobamba, periodo 2020-2021" - Sisalima Gonzalez, Karina Alexandra (2023)
The present research about "The use of software in the process of teaching and learning language in a time of pandemic in children in early childhood education II, in the school of basic education Benjamin Franklin, in the Riobamba city, period 2020- 2021", It had as main objective to analyze the use of educational software for the development of communication skills in the teaching-learning process since the Area understanding and expression of language is of almost importance within interpersonal relationships. This research was conducted within a qualitative approach, descriptive because it allowed me to describe how virtual communication is currently with the COVID 19, supported by the bibliographic design information was collected on the variables finding their characteristics. On the other hand, the virtual fieldwork helped to gather information about a population of 25 students from the parallel "A". The techniques and instruments used were a survey the same that was applied to the parents of students, which were relevant to get a closer view of the research problem. As the analysis and interpretation of the results showed that the use of educational software in the process of teaching language learning influences the development of skills of children at the time of communicating, it is for this reason that it could be concluded that the didactic strategies that apply in the process of teaching language learning influence the development of skills of children at the time of communicating.